Upaya Kegiatan 30 Menit Baca Bersama SD N 01 Batu Payuang Kabupaten Lima Puluh Kota Meningkatkan Literasi Siswa - Halimah, Siti; Marlini, Marlini (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractThis paper discusses a 30-minute reading activity together with SD Negeri 01 Batu Payuang, Lima Puluh Kota, to improve student literacy. paper writing aims to describe; 1) the implementation of the 30-minute reading together with the habituation stage, 2) the implementation of the 30-minute reading together with the development stage, 3) the implementation of the 30-minute reading together with the learning stages. Data were collected through observation and interviews with teachers and principals in SD Negeri 01 Batu Payuang, Lima Puluh Kota. Analyzing data is done descriptively.Based on the description in the previous chapter, it can be concluded as follows. The effort of reading 30 minutes together with SD Negeri 01 Batu Payuang, Lima Puluh Kota, has improved the students' literacy quite well. First, the implementation of the 30-minute reading activity along with the refraction stage including, the reading activity 15 minutes before learning and selecting reading books in schools has been carried out well while the activities of arranging facilities and a literacy-rich environment, creating a text-rich environment, and public engagement have not been carried out properly. Second, the implementation of the 30-minute reading activity together with the development phase including, the steps of reading at the development stage, the activities of discussing stories, and the use of libraries and reading corners in schools have been carried out properly in accordance with existing guidelines, while the activities of selecting fiction and nonfiction enrichment books, non-academic assessment at the development stage, appreciating the achievements of student literacy and the formation of the School Litersi Team has not been carried out well but some of these activities are in accordance with the applicable literacy guidelines. Third, the implementation of a 30-minute reading activity together with the learning phase including, among other things, reading activities, responding to reading activities, rewriting the contents of the story carried out in accordance with predetermined guidelines, but academic assessment activities at the learning stage are still not carried out according to predetermined guidelines. As well as the impact of the implementation of the 30-minute reading together activities including positive impacts, graduates are accepted at the Faforit and Junior High Schools and enhance student learning. The negative impact is the need for parents in fulfilling reading material for students, creating a boring atmosphere and making the eyes tired for students who are not accustomed to, for parents literacy activities can waste learning time, and sometimes takes time teaching and learning process in the classroom. Third, the constraints experienced are lack of literacy facilities and understanding of teachers and school staff towards literacy activities.Keywords: literacy, program, GLS.